2018
DOI: 10.12688/f1000research.14507.1
|View full text |Cite
|
Sign up to set email alerts
|

A method for transplantation of human HSCs into zebrafish, to replace humanised murine transplantation models

Abstract: Haematopoietic stem cell (HSC) transplantation is a critical therapy for haematopoietic malignancies and immune disorders. Incomplete or delayed engraftment of HSCs in the host results in increased risk of infection and morbidity. The mechanisms of HSC engraftment are poorly understood and understanding these processes will increase transplantation success on many levels. Current animal models are immunocompromised 'humanised' mice transplanted with human HSCs. Harmful procedures include genetic manipulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Of the 1694 articles identified in Scopus, after screening, 771 articles were excluded (416 reviews, 106 publications before 2000, 50 publications in other languages, and 199 duplicated in Pubmed search), and after assessing eligibility, 910 articles were excluded (287 reported no data about HSC and 623 reported no data about noninvasive imaging); thus, only 13 articles were included from this database. In total, only 21 nonduplicate full text articles were included in this review [9,11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], as depicted in Figure 1.…”
Section: Selection Process Of the Articles Identified According To Thmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 1694 articles identified in Scopus, after screening, 771 articles were excluded (416 reviews, 106 publications before 2000, 50 publications in other languages, and 199 duplicated in Pubmed search), and after assessing eligibility, 910 articles were excluded (287 reported no data about HSC and 623 reported no data about noninvasive imaging); thus, only 13 articles were included from this database. In total, only 21 nonduplicate full text articles were included in this review [9,11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], as depicted in Figure 1.…”
Section: Selection Process Of the Articles Identified According To Thmentioning
confidence: 99%
“…Of the 21 selected studies, nine (43%) [16,[18][19][20]23,25,28,32,34] studies used mice as a cell donor for bone marrow transplant (BMT), seven studies (33%) used humans as a cell donors [9,11,21,24,26,27,33], two studies (10%) used rat cells [29,30], and the remaining studies used other cell donors, such as fish [17], axolotl [22], and dogs [31], corresponding 5% for each study. Regarding the source of the cells, the majority of studies (53%) [16,[18][19][20]23,25,[28][29][30][31][32] used bone marrow; however, the study by Ushiki [25] used bone marrow and spleen cells, and the second main source of cells was the umbilical cord used in five studies (24%) [9,11,24,27,33], followed by peripheral blood, which was used in two studies (10%) [21,26]. Furthermore, the study by Lopes [22] used liver and spleen cells, the study by Astuti [17] collected the renal marrow cells from zebrafish, and the study by Sweeney [34] obtained cells from embryonic cells.…”
Section: Extraction and Isolation Of Hematopoietic Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zebrafish develop transparent embryos ex utero with no adaptive immunity until 2 weeks of age, allowing transplant of foreign cells without the need of harmful irradiation procedures. Recent research has demonstrated that zebrafish and human primary stem cells are able to engraft within the haematopoietic niche of transplanted zebrafish embryos [83][84][85][86]. Hence, zebrafish models may provide a simpler alternative to their murine counterparts in exploring the potential efficacy of HSCT in embryos (Fig.…”
Section: Haematopoietic Stem Cell Transplantmentioning
confidence: 99%